Gene-wide tagging study of association between ABCB1 polymorphisms and multidrug resistance in epilepsy in Han Chinese. (May 2009) - Kwan, Patrick; Wong, Virginia; Ng, Ping Wing; Lui, Colin Hiu Tung; Sin, Ngai Chuen; Poon, Wai Sang; Ng, Ho Keung; Wong, Ka Sing; Baum, Larry
Aims: It remains controversial whether polymorphisms of the multidrug resistance gene ABCB1 are associated with pharmacoresistance in epilepsy. To further study the potential association, we genotyped a broad set of tagging SNPs, and explored whether any associations were affected by other host factors. We correlated any association with cerebral mRNA expression of ABCB1 .Materials & methods: A total of 12 tagging and candidate SNPs of ABCB1 were genotyped in 464 Chinese epilepsy patients (270 drug responsive, 194 drug resistant). Genotype and allele distributions in drug-responsive and drug-resistant patients were compared. ABCB1 mRNA was quantified by real-time PCR in brain samples resected from 20 patients with drug-resistant epilepsy. Its level was compared between patients with different genotypes of ABCB1 SNPs found to be associated with drug resistance.Results: The intronic polymorphism rs3789243 (p = 0.009 for allele analysis) and the coding polymorphism 2677G/T/A (p = 0.02), and haplotypes containing them, were associated with drug resistance. The 2677G/T/A genotypes remained significantly associated with drug resistance after multiple logistic regression and correction for multiple comparisons. The associations with drug resistance were found in males (p = 0.004 for rs3789243 and p = 0.0007 for 2677T/A>G) but not females, and in patients with localization-related (p = 0.006 for rs3789243 and p = 0.01 for 2677T/A>G) but not idiopathic-generalized epilepsy. ABCB1 mRNA levels did not correlate with genotypes.Conclusion: In Chinese epilepsy patients, the ABCB1 intronic polymorphism rs3789243 and the coding polymorphism 2677, and haplotypes containing them, may be associated with drug resistance, without an effect on mRNA expression. There was preliminary evidence of interactions between these polymorphisms and gender and epilepsy syndrome.